2016
DOI: 10.1037/com0000035
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the “secret” of play in dogs (Canis lupus familiaris): Asymmetry and signals.

Abstract: Due to their playful propensity, dogs are a good model to test some hypotheses about play dynamics (length, asymmetry, features of players) and communication (play bow [PBOW]; relaxed open-mouth [ROM] display). We video-recorded 203 play sessions between dogs in an off-leash dog park in Palermo, Italy. Contrary to the expectation, play asymmetry (particularly high in this species) did not differ between stranger and familiar dogs, thus suggesting the limited role of play in forming dominance relationships. Asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 52 publications
0
35
0
Order By: Relevance
“… 35 ). To date, functional facial expressions in dogs have been largely discussed holistically in relation to their approach-avoidance value, for example, the “threat gape” in fight-flight situations 3 , and the PF or the Relaxed Open Mouth (ROM) as a social communicative signal for play solicitation and within play bouts 3 , 36 , 37 . With the development of the FACS for the domestic dog 24 , it becomes possible to apply a bottom-up technique to investigate the composition and meaning of dogs’ facial expressions and, more importantly, to establish possible analogies with humans, with whom they socially interact.…”
Section: Introductionmentioning
confidence: 99%
“… 35 ). To date, functional facial expressions in dogs have been largely discussed holistically in relation to their approach-avoidance value, for example, the “threat gape” in fight-flight situations 3 , and the PF or the Relaxed Open Mouth (ROM) as a social communicative signal for play solicitation and within play bouts 3 , 36 , 37 . With the development of the FACS for the domestic dog 24 , it becomes possible to apply a bottom-up technique to investigate the composition and meaning of dogs’ facial expressions and, more importantly, to establish possible analogies with humans, with whom they socially interact.…”
Section: Introductionmentioning
confidence: 99%
“…A first attempt to characterize turn taking in play fighting was the 50:50 rule (Altmann, 1962), which implies that, for play fighting to remain playful, the animals have to have equal chances of gaining the advantage (Dugatkin & Bekoff, 2003). Subsequent empirical studies have shown that play fighting can be substantially asymmetrical and still remain playful (Bauer & Smuts, 2007;Cordoni, Nicotra, & Palagi, 2016;Pellis, Pellis, & McKenna, 1993), although not if one partner completely dominates the interactions (Suomi, 2005;Wilmer, 1991). Thus, although the degree of reciprocity, or turn taking, can vary markedly with the species, age, sex, and dominance status of the participants (e.g., Bauer & Smuts, 2007;Biben, 1998;Cordoni & Palagi, 2011;Pellis et al, 1993), at least some degree of reciprocity is needed to sustain play (Bekoff, 2014;Palagi, Cordoni, Demuru, & Bekoff, 2016), and this is true whether the play fighting is derived from sex or aggression (Pellis & Pellis, 1988a, 1988bReinhart et al, 2010).…”
Section: It Is Not What You Compete For But How You Compete That Matmentioning
confidence: 99%
“…A play session is the outcome of cooperative and competitive elements that can be measured and quantified [ 22 , 23 ]. The way the session is built up is predictive of its function (for review [ 12 ]).…”
Section: Introductionmentioning
confidence: 99%
“…The short-term adaptive functions of play can be related to the level of cooperation and tolerance of the species considered [ 24 ]. For example, adult play rates generally covary with the level of tolerance and social affiliation characterizing the group (ungulates, [ 25 ]; rodents, [ 26 ]; canids, [ 22 , 27 ]; primates, [ 28 , 29 ]). Inter-individual tolerance favors the retention of play also during the adult phase, thus suggesting that this behavior can provide benefits also during adulthood [ 10 , 30 ].…”
Section: Introductionmentioning
confidence: 99%